2D-HEC-RAS Modeling of Flood Wave Propagation in a Semi-Arid Area Due to Dam Overtopping Failure - Karim, Ibtisam R.; Hassan, Zahraa F.; Abdullah, Hassan Hussein; Alwan, Imzahim A. (Civil Engineering Journal, 2021)
Dam overtopping failure and the resulting floods are hazardous events that highly impact the inundated areas and are less predictable. The simulation of the dam breach failure and the flood wave propagation is necessary for assessing flood hazards to provide precautions. In the present study, a two-dimensional HEC-RAS model was used to simulate the flood wave resulting from the hypothetical failure of Al-Udhaim Dam on Al-Udhaim River, Iraq, and the propagation of the resulting dam-break wave along 100 km downstream the dam site for the overtopping scenario. The main objective is to analyze the propagation of the flood wave so that the failure risk on dam downstream areas can be assessed and emergency plans may be provided. The methodology consisted of two sub-models: the first is the dam breach failure model for deriving the breach hydrograph, and the second is the hydrodynamic model for propagating the flood wave downstream of the dam. The breach hydrograph is used as an upstream boundary condition to derive the flood impact in the downstream reach of Al- Udhaim River. The flood inundation maps were visualized in RAS-Mapper in terms of water surface elevation, water depth, flow velocity, and flood arrival time. The maximum recorded values were: 105 m (a.m.s.l.), 18 m, 5.5 m/s, and, respectively. The flow velocity decreased from upstream to downstream of the terrain, which means less risk of erosion in the far reaches downstream of the study area. The inundation maps indicated that the water depth and flow velocity were categorized as Catastrophic limits on the terrain's area. The results offer a way to predict flood extent and showed that the impact of a potential dam break at Al-Udhiam Dam will be serious, therefore, suitable management is needed to overcome this risk. Moreover, the maps produced by this study are useful for developing plans for sustainable flood management.Â Doi: 10.28991/cej-2021-03091739 Full Text: PDF